Rapid Perceptual Learning: A Potential Source of Individual Differences in Speech Perception Under Adverse Conditions? - Rotman, Tali (Trends Hear, 2020)
Challenging listening situations (e.g., when speech is rapid or noisy) result in substantial individual differences in speech perception. We propose that rapid auditory perceptual learning is one of the factors contributing to those individual differences. To explore this proposal, we assessed rapid perceptual learning of time-compressed speech in young adults with normal hearing and in older adults with age-related hearing loss. We also assessed the contribution of this learning as well as that of hearing and cognition (vocabulary, working memory, and selective attention) to the recognition of natural-fast speech (NFS; both groups) and speech in noise (younger adults). In young adults, rapid learning and vocabulary were significant predictors of NFS and speech in noise recognition. In older adults, hearing thresholds, vocabulary, and rapid learning were significant predictors of NFS recognition. In both groups, models that included learning fitted the speech data better than models that did not include learning. Therefore, under adverse conditions, rapid learning may be one of the skills listeners could employ to support speech recognition.